ANALISIS FINANCIAL DISTRESS DENGAN MODEL ALTMAN Z-SCORE SEBELUM DAN SAAT TERJADINYA PANDEMI COVID-19 - Kurniasih, Yuli (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2022)
The purpose of this research is to compare the financial distress of companies in the restaurant, hotel, and tourism sub-sector before and after the Covid-19 pandemic, as well as to predict the future of these industries. Purposive sampling was used to collect the sample data. Secondary data collected through documentation methods was used for this analysis. The data analyzed using the modified Altman Z-Score discriminant ratio method and tested using the Wilcoxon Signed Rank Test. Companies in the restaurants, hotels, and tourism sub sector experienced a higher rate of financial distress during the Covid-19 pandemic than before, according to the available data.